Subjective Meaning of Strategic Pricing Decision Making based on Islamic Values in the Muslim Business community - junaedi, wahyu; Prihanisetyo, Adi (IQTISHADIA, 2022)
Fierce competition in business often encourages businesses to act unreasonably in their pricing strategies. Orientation to maximum profit often trumps the ethical values derived from religious teachings. This study aims to find the meaning of strategic pricing decision-making of Muslim businessmen based on their awareness of Islamic values. Islamic values arise from the perception of business people as a reflection of knowledge about Islamic ethics that they understand. The research method used is transcendental phenomenology. The sampling was conducted on five businesspeople members of the Indonesian Islamic Business Forum (IIBF).  This study found that Muslim businessmen Interpret strategic pricing decision-making according to their awareness of Islamic values as a form of justice, namely fairness in pricing based on market segments and based on product value-added. This research will provide knowledge to business people to consider ethics in the strategic policy of price management conducted.